A Secure and Reliable Fog-Enabled Architecture Using Blockchain With Functional Biased Elliptic Curve Cryptography Algorithm for Healthcare Services - charu awasthi; Satya Prakash; Prashant Kumar Mishra (Blockchain in Healthcare Today)
Fog computing is an emerging technology that extends the capability and efficiency of cloud computing networks by acting as a bridge among the cloud and the device. Fog devices can process an enormous volume of information locally, are transportable, and can be deployed on a variety of systems. Because of its real-time processing and event reactions, it is ideal for healthcare. With such a wide range of characteristics, new security and privacy concerns arise. Due to the safe transmission, arrival, and access, as well as the availability of medical devices, security creates new issues in the area of healthcare. As an outcome, fog computing necessitates a unique approach to security and privacy metrics, as opposed to standard cloud computing methods. Hence, this paper suggests an effective blockchain depending on secure healthcare services in fog computing. Here the fog nodes gather the information from the medical sensor devices and the data is validated using smart contracts in the blockchain network. We propose a Functional Biased Elliptic Curve Cryptography Algorithm (FB-ECC) to encrypt the data. The optimization is performed using Galactic Bee Colony Optimization Algorithm (GBCOA) to enhance the procedure of encryption. The performance of the suggested methodology is assessed and contrasted with the traditional techniques. It is proved that the combination of fog computing with blockchain has increased the security of data transmission in healthcare services